Public danger of crime: the concept and criteria of verification - N. A. Lopashenko; A. V. Golikova; E. V. Kobzeva; D. A. Kovlagina; M. M. Lapunin; K. M. Khutov (Правоприменение, 2021)
The subject. The article reveals theoretical, lexical and logical approaches to determining the essence of the public danger of crime.The purpose of the article is to confirm or dispute hypothesis that the public danger of crime as a legal or theoretical construction represents the possibility of negative changes in society; public danger is an exclusive social feature of criminal acts. The authors also aim to develop a system of verifiable criteria for public danger.The methodology of the research is an objective assessment of the public danger as legal category. It is performed selecting a system of verified factors of public danger on the basis of analysis and synthesis, induction and deduction, interpretation of legal literature.The main results, scope of application. The meaning of the legal definition of a crime contains the purpose of preventing possible harm to society stipulated in the criminal law. This fact is due to the preventive task (part 1 of article 2 of the Russian Criminal Code). The public danger of crime as a phenomenon of objective reality is meaningless, since the crime is the negative changes and harm that has occurred. The social danger of crime creates a shock to the foundations of society, undermines the conditions of its existence. Other ("non-criminal") offenses that contradict the established law and order in the state do not threaten the basic system of social values. Intersectoral differentiation of legal responsibility should have transitivity, which includes a rule: the degree of repression of coercive measures within various branches of law meets the rules of hierarchy. Mandatory signs of public danger of a crime are that the act: 1) affects significant social relations that need criminal legal protection from causing harm to them by socially dangerous behavior; 2) has a harmful potential that is fraught with causing significant harm or creating a threat of causing such harm to the object of criminal legal protection; 3) results in socially dangerous consequences; 4) is characterized by the guilty attitude of the subject to the deed, expressed in the form of intent or carelessness. Optional criteria of public danger of act are: the characteristics of the crime and characteristics of victim; method of committing a crime; the time, place, atmosphere, instruments and means of committing the crime; the motive; the object of the crime; special characteristics of the perpetrator. The quantitative indicators (size, severity, or other value) of the subject of the offense and its socially dangerous consequences, as well as the repetition of the act and the presence of a special recidivism of crimes should not be used as criteria for public danger of behavior.Conclusions. Public danger is a social feature exclusively of criminal acts (crimes and potential criminal misdemeanors); all other types of offenses are harmful to the interests of society, but they do not pose a danger to it. To exclude competition between criminal and administrative responsibility, it is necessary to take into account the public danger of the crime on the basis of verifiable factors.